MODELLING OF VOLCANIC ERUPTIONS ON TITAN - Solomonidou, A.; Fortes, A.D.; Kyriakopoulos, K. (Bulletin of the Geological Society of Greece, 2010)
Observations by the Visual Infrared Spectrometer instrument (VIMS) aboard the Cassini mission have indicated the possible presence of CO2 ice on the surface on Titan, in areas which exhibit high reflectance in specific spectral windows (McCord et al., 2008). Two of the bright spots of significance are located within the Xanadu region – Tui Regio (located at 20°S, 130°W) and Hotei Regio (located at 26°S, 78°W), and there is a further spot situated in proximity to Omacatl Macula (Hayne et al., 2008). Explosive volcanic eruptions of a cryomagma containing H2O and CO2 are modelled for several potential scenarios regarding entrained CO2 clathrates. The model yielded a range of values corresponding to the fragmentation pressure in the lava conduit, the velocity of the exploding cryomagma, the height of the associated lava fountain and the potential distance covered by ejecta. The results show that a single vent source does not possess the force required to cover an area resembling Hotei Regio or Tui Regio. Therefore, we consider alternative origins: the area may have been resurfaced by small CO2 grains resulting from multiple explosive eruptions emanating from a zone of weakness (Hayne et al., 2008); the characteristics of the area are consequential of an eruption of cryomagma with CO2 and NH3 components (McCord et al., 2008); or finally, long term seasonal winds transferred small CO2 grains and distributed them within the limits of Tui Regio area.